Diviners, malams, god, and the contest for paramount chiefship in Mamprugu (Northern Ghana) - Tonah, S. (Anthropos: International Review of Anthropology and Linguistics, 2006)
This article analyses the contest for paramount chiefship in Mamprugu, one of the traditional states in northern Ghana. It examines the role that spiritualists such as diviners and malams play in the contest. The first part provides an overview of Mamprusi traditional political system and the province of Wungu, from which this case study is taken. This is followed by an analysis of Traditional African Religion and Islam, the two dominant religious practices in the area. Finally, the article examines the contest for paramount chiefship in 2001 and the specific role that spiritualists such as diviners and malams play during the contest.